Capillary electromigration separation of proteins and microorganisms dynamically modified by chromophoric nonionogenic surfactant - Horká, Marie; Růžička, Filip; Holá, Veronika; Kahle, Vladislav; Moravcová, Dana; Šlais, Karel (Analytical chemistry, 2009)
A chromophoric nonionogenic surfactant poly(ethylene glycol) 3-(2-hydroxy-5-n-octylphenylazo)-benzoate, HOPAB, has been prepared and used as a buffer additive for a dynamic modification of proteins and/or microorganisms including Escherichia coli , Staphylococcus epidermidis (biofilm-positive and biofilm-negative), and the strains of yeast cells Candida albicans and Candida parapsilosis (biofilm-positive and biofilm-negative) during a capillary electrophoresis and a capillary isoelectric focusing (CIEF) with UV detection at 326 nm. Values of isoelectric points of labeled proteins and microorganisms have been calculated using UV-detectable pI markers and have been found comparable with pI of the native compounds. Minimum detectable amount has been assessed lower than picograms of proteins and lower than a hundred cells injected into a separation capillary. The introduced labeling method facilitates CIEF separation of microorganisms from the clinical sample of the infected urine at their clinically important levels in the pH gradient pH range of 2-5 and their subsequent cultivation. At the same time, it has enabled the determination of albumin in human urine as a major clinical marker of urinary tract infections and kidney diseases.
Keywords: bakteriální proteiny; Isoelectric Focusing; isoelektrická fokusace; Bacterial Proteins; povrchově aktivní látky; lidé; Fungal Proteins; Electrophoresis, Capillary; spektrofotometrie ultrafialová; fungální proteiny; Spectrophotometry, Ultraviolet; elektroforéza kapilární; Surface-Active Agents; Humans